European Funds and Firm Performance: Evidence from a Natural Experiment - José Mesquita; Jo\~ao Pereira dos Santos; José Tavares (Institute of Labor Economics (IZA), 2023)
This paper analyses the impact of European Union (EU) funds on the performance of private firms. In particular, we examine a quasi-natural experiment consisting of a redrawing of administrative areas that expanded regional eligibility and led to a sudden increase in accessibility to EU grants for firms located in 33 Portuguese municipalities. Using a comprehensive linked employer-employee administrative dataset that covers the universe of private firms between 2003 and 2010, our difference-in-differences estimates uncover a significant and positive causal effect of increased eligibility on firms' sales, labour productivity, and average wages, while employment is not significantly altered. While firms' sales in the non-tradable sectors are positively impacted, firms' sales in more competitive, tradable, sectors remain unaffected by increased access to EU funds.
Keywords: C21; R10; 330; grants; regional policy; private firm; municipalities; Portugal